VARIASI DOSIS PUPUK KOTORAN AYAM PADA BUDIDAYA CACING RAMBUT (Tubifex sp) - Herliwati Herliwati (Fish Scientiae, 2019)
The aim of research is to know the efective level of chicken feces dosage for tubificidian culture. The simple random sampling on three levels dosage of chichenfeces (ratio of chicken feces and soil) with three replication each was used in theresearch. The level dosage C (30 g/2500 g) has give the faster growth of tubificidian compared with level dosage A (10 g/2500 g) and level dosage B (20 g/2500 g).